An Analysis of Judicial Considerations of the Capitalist Economy in the Tom Lembong Case - Saputra, M. Reza; Hilyatunisa, Nabila (PT. Riset Press International, 2025)
This study examines the intersection of economic ideology and criminal adjudication in the sugar-import licensing case of former Indonesian Trade Minister Thomas Trikasih Lembong. In July 2025, the Jakarta Corruption Court convicted Lembong for alleged corruption in sugar import permits, citing his prioritisation of market-oriented policies referred to as a “capitalist economic approach” as an aggravating factor. Subsequently, President Prabowo Subianto granted Lembong presidential abolition, terminating all legal proceedings and restoring his reputation. Employing a qualitative, document-analytical methodology, this research systematically reviews judicial opinions, ministerial decrees, and expert commentary to assess (1) the extent to which neoliberal ideology influenced the court’s reasoning; (2) the legality of treating economic policy choices as criminal conduct; and (3) the broader ramifications for Indonesia’s Democratic Economic System. Critical discourse analysis reveals that the court’s invocation of capitalism as a quasi-legal standard lacks constitutional or statutory basis and undermines the mens rea requirement central to criminal law. Key informants including former Coordinating Minister Mahfud MD and public commentator Ferry contend that ideological characterisations are non-justiciable absent clear legislative prohibition. The verdict risks engendering policy paralysis by conflating administrative discretion with criminal liability, thereby deterring innovative market reforms and eroding investor confidence. Despite the remedial effect of presidential abolition, the precedent endures within judicial discourse, posing systemic challenges to policy transparency and regulatory predictability. The study concludes with recommendations for judicial restraint and legislative clarification to delineate policy critique from criminal prosecution, safeguarding institutional integrity and enabling adaptive economic governance in an evolving global environment.